Silicon carbide ceramic printing material and preparation method thereof, and silicon carbide ceramic product
By spheroidizing and presintering the silicon carbide powder and mixing it with a wax-based binder, a silicon carbide ceramic printing material with low porosity and high dimensional accuracy is prepared, which solves the problems of warping, deformation and cracking of silicon carbide ceramic products in the prior art, and achieves high precision and low porosity of the products.
Patent Information
- Application Number
- CN202411868966.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-04-04
AI Technical Summary
Existing silicon carbide ceramic printing products are prone to problems such as warping, deformation, and cracking, and have low dimensional accuracy, high porosity and low density.
By mixing silicon carbide powder, sintering aid and organic binder, spherical treatment and pre-sintering treatment, spherical particles are prepared, and then mixed with wax-based binder, kneading and granulating treatment, silicon carbide ceramic printing material with low porosity and high dimensional accuracy is prepared.
The low porosity and high dimensional accuracy of silicon carbide ceramic products are achieved, which reduces internal stress and improves the stability and uniformity of printing materials, providing a good foundation for the melt deposition and forming of large-size silicon carbide ceramic products.
Smart Images

Figure CN119751076A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of silicon carbide ceramic materials, and in particular to a silicon carbide ceramic printing material and a preparation method thereof, and a silicon carbide ceramic product. Background Art
[0002] Silicon carbide ceramics have the characteristics of stable chemical properties, high thermal conductivity, low thermal expansion coefficient, low density, good wear resistance, high hardness, high mechanical strength, and chemical corrosion resistance. They are widely used in ceramic ball bearings, valves, semiconductor materials, gyroscopes, measuring instruments, aerospace and other fields. The overall preparation of large and complex silicon carbide ceramic components is of great significance to the development of technologies such as aerospace, military industry, new energy and semiconductors. However, due to the characteristics of silicon carbide ceramic materials such as strong defect sensitivity, large deformation during high-temperature sintering, and difficulty in processing after sintering, the overall preparation and industrialization of large and complex silicon carbide ceramic components have become technical problems.
[0003] Ceramic additive manufacturing can achieve rapid manufacturing of silicon carbide ceramics with complex structures, bringing new ideas for lightweight and customized silicon carbide products for aerospace and nuclear industries. Compared with additive manufacturing technologies such as laser powder additive manufacturing and photocuring ceramic printing, fused deposition modeling of silicon carbide ceramics has the advantages of small forming thermal stress, low printing equipment cost, and high sintering density of printed products. It has become the preferred method for additive manufacturing of silicon carbide ceramics. Fused deposition modeling of silicon carbide is a process of mixing a plastic binder with silicon carbide ceramic powder, which is then extruded through a screw at the temperature where the binder is molten, and imported through a digital model to achieve layer-by-layer deposition and printing; the printed silicon carbide ceramic body is then degreased and sintered to obtain a 3D silicon carbide ceramic product.
[0004] At present, there have been reports on the use of fused deposition modeling to prepare silicon carbide ceramics, but the printed products are still prone to warping, deformation, cracking, etc., and their dimensional accuracy is low; and the products have high porosity and low density. Therefore, it is necessary to further improve the traditional silicon carbide ceramic printed products. Summary of the invention
[0005] Based on this, one or more embodiments of the present application provide a silicon carbide ceramic printing material and a preparation method thereof. The silicon carbide ceramic product made using the above printing material has the advantages of low porosity and high dimensional accuracy.
[0006] According to the first aspect of the present application, a method for preparing a silicon carbide ceramic printing material is provided, comprising the following steps:
[0007] The silicon carbide powder, sintering aid and organic binder are mixed and spheroidized to obtain composite particles;
[0008] Pre-sintering the composite particles to obtain spherical particles;
[0009] The spherical particles are mixed with a wax-based binder, and kneading and granulation are performed in sequence to obtain the silicon carbide ceramic printing material;
[0010] Among them, calculated by mass percentage, the wax-based adhesive includes 85% to 92% wax adhesive, 5% to 8% backbone adhesive and 1% to 8% dispersant, the melting index of the backbone adhesive is 0.1 g / 10min to 0.5 g / 10min, and the average molecular weight of the backbone adhesive is 1 million to 1.5 million.
[0011] In one embodiment, the preparation method meets one or more of the following characteristics:
[0012] (1) The backbone binder includes one or more of ultra-high molecular weight polypropylene and ultra-high molecular weight polyethylene;
[0013] (2) The wax binder includes one or more of carnauba wax, paraffin wax and microcrystalline wax;
[0014] (3) The dispersant includes one or more of stearic acid, zinc stearate and epoxy resin.
[0015] In one embodiment, the spheroidization treatment includes one or more of spray granulation and ultrasonic spray drying;
[0016] Optionally, the temperature of the spray granulation is 80°C to 120°C.
[0017] In one embodiment, the preparation method meets one or more of the following characteristics:
[0018] (1) The D50 particle size of the silicon carbide powder is 0.2 μm to 2 μm;
[0019] (2) The D50 particle size of the composite particles is 20 μm to 200 μm;
[0020] (3) The average particle size of the spherical particles is 50 μm to 100 μm.
[0021] In one embodiment, the preparation method meets one or more of the following characteristics:
[0022] (1) The sintering aid includes one or more of boric acid, boron, boron carbide, yttrium oxide and aluminum oxide;
[0023] (2) The organic binder includes one or more of polyvinyl alcohol, polyethylene glycol, methyl cellulose and polyacrylic acid.
[0024] In one embodiment, the preparation method meets one or more of the following characteristics:
[0025] (1) Based on the total mass of silicon carbide powder, the amount of the sintering aid added is 0.2wt%~2wt%;
[0026] (2) Based on the total mass of the silicon carbide powder, the amount of the organic binder added is 0.1wt%~0.5wt%.
[0027] In one embodiment, the preparation method meets one or more of the following characteristics:
[0028] (1) The pre-sintering treatment is performed at a temperature of 1000°C to 1400°C and for a time of 30 min to 120 min;
[0029] (2) The mixing process is performed at a temperature of 120°C to 180°C and for a time of 40 min to 80 min;
[0030] (3) The nozzle temperature of the granulation process is 120°C to 140°C, and the screw temperature is 120°C to 150°C.
[0031] In one embodiment, based on the total volume of the spherical particles and the wax-based binder, the spherical particles account for 58 vol% to 65 vol%, and the wax-based binder accounts for 35 vol% to 42 vol%.
[0032] According to a second aspect of the present application, a silicon carbide ceramic printing material is provided, which is prepared by the above-mentioned method for preparing the silicon carbide ceramic printing material.
[0033] According to a third aspect of the present application, a silicon carbide ceramic product is provided, and the raw materials for preparing the silicon carbide ceramic printing material include the above-mentioned silicon carbide ceramic printing material.
[0034] Compared with the traditional technology, this application has the following beneficial effects:
[0035] The present application performs spheroidization and pre-sintering treatment on silicon carbide powder to obtain spherical particles with low specific surface area and good fluidity, thereby reducing the amount of wax-based binder used to coat the spherical particles and making the silicon carbide powder less prone to breakage during the mixing process. At the same time, the wax binder is combined with a small amount of low melt index, high molecular weight backbone binder to form a wax-based binder with high fluidity and low crystallinity. The wax-based binder can improve the fluidity and diffusivity of the printed material during the printing process, thereby reducing the interlayer porosity of the product and improving the dimensional accuracy. Furthermore, the above-mentioned wax-based binder of the present application is combined with spherical particles to reduce the internal stress of the printed material, providing a good foundation for the melt deposition forming of large-size silicon carbide ceramic products. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0037] Figure 1 This is a morphology diagram of the silicon carbide ceramic product obtained in Example 1 of the present application;
[0038] Figure 2 This is a morphology diagram of the silicon carbide ceramic product prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0039] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.
[0041] Fused deposition modeling of silicon carbide ceramics involves mixing silicon carbide ceramic powder with a sintering aid and a binder through an internal mixer, then granulating the particles to obtain printing feed particles, and then extruding the feed through a printing device to obtain silicon carbide ceramics.
[0042] In traditional technology, the preparation of silicon carbide ceramics by fused deposition forming mainly has the following problems: (1) Deposition forming is formed by stacking layers. Due to the rapid solidification of the extruded wire diameter, interlayer defects (such as triangular holes) are prone to occur, thereby reducing the mechanical strength of silicon carbide ceramics. (2) Silicon carbide ceramic powders are usually micron or submicron in size to improve sintering activity, but the fluidity of ultrafine powders is poor, resulting in a high proportion of binder in the silicon carbide ceramic printing feed; the binder has a certain volume shrinkage from the molten state to the solidified state, and a high content of binder will bring greater thermal stress to the printed blank, causing warping and deformation of the printed blank, thereby reducing the stability of the printing process and the dimensional accuracy of the component.
[0043] However, the above two factors restrict each other, and it is challenging to solve the two problems at the same time. If you want to reduce the defects between deposited layers, you generally need to increase the binder content in the feed to improve its fluidity and promote the mutual fusion of deposited lines; but too high a binder content will increase the thermal stress of the deposition process, causing more serious cracking between sample layers or sample warping.
[0044] Based on this, the present application proposes a new silicon carbide ceramic printing material and a preparation method thereof to solve the above technical problems.
[0045] In a first aspect of the present application, a method for preparing a silicon carbide ceramic printing material is provided, comprising S10 to S30.
[0046] S10: mixing silicon carbide powder, a sintering aid and an organic binder, and preparing composite particles by spheroidizing;
[0047] S20: pre-sintering the composite particles to obtain spherical particles;
[0048] S30: mixing the spherical particles with the wax-based binder, and sequentially performing a mixing process and a granulation process to obtain a silicon carbide ceramic printing material;
[0049] Among them, calculated by mass percentage, the wax-based binder includes 85%~92% wax binder, 5%~8% backbone binder and 1%~8% dispersant. The melt index of the backbone binder is 0.1g / 10min~0.5g / 10min, and the average molecular weight of the backbone binder is 1 million~1.5 million.
[0050] The present application mixes silicon carbide powder, a sintering aid and an organic binder, and obtains nearly spherical composite particles through spheroidization treatment, so that the specific surface area thereof is reduced, thereby being able to reduce the amount of wax-based binder used and increase the solid content in the final printed material; at the same time, a granular material with good fluidity is obtained through spheroidization treatment and pre-sintering treatment, so that it is not easy to break during the mixing process; the nearly spherical composite particles can maintain good sintering activity.
[0051] The wax-based binder of the present application comprises a wax binder with a high mass ratio and a low-fluidity backbone binder, which can promote the secondary flow and diffusion of the printed material during the printing process, thereby reducing the interlayer porosity during the printing process and improving the dimensional accuracy of the product. The wax binder is an amorphous binder, which can further reduce the thermal stress between the blanks, accelerate the solvent degreasing rate, and further obtain a connected thermal degreasing channel to avoid the appearance of microcracks in the blanks during the sintering process; the low-fluidity backbone binder can improve the strength of the blanks during the solvent degreasing process.
[0052] The wax-based binder of the present application can be combined with spherical particles to reduce the internal stress of the printed material, improve the stability and uniformity of the printed material, and provide a good foundation for the molten deposition forming of large-sized silicon carbide ceramic products.
[0053] In some embodiments, in S10, the D50 particle size of the silicon carbide powder is 0.2μm~2μm; as an example, the average particle size of the silicon carbide powder can be 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, or any value within the range formed by any two of the above point values.
[0054] Furthermore, the D50 particle size of the silicon carbide powder is 0.5 μm to 1 μm.
[0055] In some embodiments, in S10, the D50 particle size of the composite particles is 20 μm to 200 μm; as an example, the average particle size of the composite particles can be 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105μm, 110μm, 115μm, 120μm, 125μm, 130μm, 135μm, 140μm, 145μm, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, 200μm, or any value within the range formed by any two of the above point values.
[0056] Furthermore, the D50 particle size of the composite particles is 50 μm to 100 μm.
[0057] In the present application, "D50 particle size" is the median particle size, which refers to the particle size corresponding to when the cumulative particle size distribution percentage in a particle group reaches 50%.
[0058] In some embodiments, in S10, the sintering aid includes one or more of boric acid, boron, boron carbide, yttrium oxide, and aluminum oxide.
[0059] In some embodiments, the amount of the sintering aid added is 0.2 wt% to 2 wt% based on the total mass of the silicon carbide powder. As an example, the amount of the sintering aid added can be 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2.0 wt%, or any value within the range formed by any two of the above point values.
[0060] Furthermore, the added amount of the sintering aid is 0.5wt%~1wt%.
[0061] In some embodiments, in S10, the organic binder includes one or more of polyvinyl alcohol, polyethylene glycol, methyl cellulose and polyacrylic acid.
[0062] In some embodiments, the amount of the organic binder added is 0.1 wt% to 0.5 wt% based on the total mass of the silicon carbide powder. As an example, the amount of the organic binder added can be 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, or any value within the range formed by any two of the above point values.
[0063] In some embodiments, in S10, the spheroidization treatment includes one or more of spray granulation and ultrasonic spray drying.
[0064] In the spray granulation process, when the crystals are very small, due to the large surface energy of the grains, the small grains are easily combined together due to weak interaction forces, resulting in agglomeration between the grains to form larger particles.
[0065] In some embodiments, in S10, the temperature of the spray granulation is 80° C. to 120° C. As an example, the temperature of the spray granulation can be 80° C., 81° C., 82° C., 83° C., 84° C., 85° C., 86° C., 87° C., 88° C., 89° C., 90° C., 91° C., 92° C., 93° C., 94° C., 95° C., 96° C., 97° C., 98° C., 99° C., 100° C., 101° C., 102° C., 103° C., 104° C., 105° C., 106° C., 107° C., 108° C., 109° C., 110° C., 111° C., 112° C., 113° C., 114° C., 115° C., 116° C., 117° C., 118° C., 119° C., 120° C., or any value within the range formed by any two of the above point values.
[0066] In some embodiments, in S20, the temperature of the pre-sintering treatment is 1000°C to 1400°C, and the time is 30min to 120min. As an example, the temperature of the pre-sintering treatment can be 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, or any value within the range formed by any two of the above point values. As an example, the time of the pre-sintering treatment can be 30min, 35min, 40min, 45min, 50min, 55min, 60min, 65min, 70min, 75min, 80min, 85min, 90min, 95min, 100min, 105min, 110min, 115min, 120min, or any value within the range formed by any two of the above point values.
[0067] In some embodiments, in S20, the average particle size of the spherical particles is 50 μm to 100 μm.
[0068] As an example, the average particle size of the spherical particles can be 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, or any value within the range formed by any two of the above point values.
[0069] In some embodiments, in S30, the temperature of the mixing process is 120°C to 180°C, and the time is 40min to 80min. As an example, the temperature of the mixing process can be 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, or any value within the range formed by any two of the above point values; as an example, the time of the mixing process can be 40min, 45min, 50min, 55min, 60min, 65min, 70min, 75min, 80min, or any value within the range formed by any two of the above point values.
[0070] In some embodiments, in S30, the nozzle temperature of the granulation process is 120°C to 140°C, and the screw temperature is 120°C to 150°C. As an example, the nozzle temperature of the granulation process can be 120°C, 122°C, 124°C, 126°C, 128°C, 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, or any value within the range of any two of the above point values. As an example, the screw temperature of the granulation process can be 120°C, 122°C, 124°C, 126°C, 128°C, 130°C, 132°C, 134°C, 136°C, 138°C, 140°C, 142°C, 144°C, 146°C, 148°C, 150°C, or any value within the range of any two of the above point values.
[0071] In this application, "nozzle temperature" refers to the temperature of the nozzle part located at the end of the extruder; "screw temperature" refers to the temperature of the extruder screw.
[0072] In some embodiments, in S30, the wax binder includes one or more of carnauba wax, paraffin wax and microcrystalline wax. Optionally, the wax binder is selected from carnauba wax.
[0073] In some embodiments, in S30, the dispersant includes one or more of stearic acid, zinc stearate and epoxy resin. Optionally, the dispersant is selected from stearic acid.
[0074] As an example, in S30, the mass percentage of the wax adhesive in the wax-based adhesive can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, or any value within the range formed by any two of the above point values.
[0075] Furthermore, the mass percentage of the wax binder is 88% to 92%; further, the mass percentage of the wax binder is 90% to 92%.
[0076] As an example, in S30, the mass percentage of the backbone binder in the wax-based binder may be 5%, 6%, 7%, 8%, or any value within the range formed by any two of the above point values.
[0077] Furthermore, the mass percentage of the backbone binder is 5% to 7%.
[0078] As an example, in S30, the mass percentage of the dispersant in the wax-based binder can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, or any value within the range formed by any two of the above point values.
[0079] Furthermore, the mass percentage of the dispersant is 1% to 5%.
[0080] As an example, in S30, the melt index of the backbone binder is 0.1 g / 10 min, 0.2 g / 10 min, 0.3 g / 10 min, 0.4 g / 10 min, 0.5 g / 10 min, or any value within the range formed by any two of the above point values.
[0081] Understandably, the smaller the melt index of the backbone binder, the lower its fluidity.
[0082] As an example, in S30, the average molecular weight of the backbone binder is 1 million, 1.01 million, 1.02 million, 1.03 million, 1.04 million, 1.05 million, 1.06 million, 1.07 million, 1.08 million, 1.09 million, 1.10 million, 1.11 million, 1.12 million, 1.13 million, 1.14 million, 1.15 million, 1.16 million, 1.17 million, 1.18 million, 1.19 million, 1.20 million, 1.21 million, 1.22 million, 1.23 million, 1.24 million, 1.26 million, 1.27 million, 1.28 million, 1.29 million, 1.30 million, 1.31 million, 1.32 million, 1.33 million, 1.34 million, 1.36 million, 1.37 million, 1.38 million, 1.39 million, 1.40 million, 1.41 million, 1.42 million, 1.43 million, 1.44 million, 1.47 million, 1.48 million, 1.49 million, 1.50 million, 1.51 million, 1.52 million, 1.53 million, 1.54 million, 1.55 million, 1.56 million, 1.57 million, 1.58 million, 1.59 million, 1. 50,000, 1.26 million, 1.27 million, 1.28 million, 1.29 million, 1.30 million, 1.31 million, 1.32 million, 1.33 million, 1.34 million, 1.35 million, 1.36 million, 1.37 million, 1.38 million, 1.39 million, 1.40 million, 1.41 million, 1.42 million, 1.43 million, 1.44 million, 1.45 million, 1.46 million, 1.47 million, 1.48 million, 1.49 million, 1.50 million, or any value within the range formed by any two of the above point values.
[0083] In some embodiments, in S30, the backbone binder includes one or more of ultra-high molecular weight polypropylene (UHMWPP) and ultra-high molecular weight polyethylene (UHMWPE).
[0084] In some embodiments, the backbone binder includes ultra-high molecular weight polypropylene and ultra-high molecular weight polyethylene; further, the mass ratio of the ultra-high molecular weight polypropylene to the ultra-high molecular weight polyethylene is 1:1.
[0085] Understandably, low-fluidity backbone binders can improve the strength of the blank during solvent degreasing and reduce cracking and breakage of the final product.
[0086] In some embodiments, in S30, based on the total volume of the spherical particles and the wax-based binder, the spherical particles account for 58 vol% to 65 vol%, and the wax-based binder accounts for 35 vol% to 42 vol%.
[0087] As an example, the volume fraction of spherical particles can be 58 vol%, 59 vol%, 60 vol%, 61 vol%, 62 vol%, 63 vol%, 64 vol%, 65 vol%, or any value within the range formed by any two of the above point values. Further, the volume fraction of spherical particles is 60 vol% to 65 vol%.
[0088] The volume fraction of the wax-based binder may be 35 vol%, 36 vol%, 37 vol%, 38 vol%, 39 vol%, 40 vol%, 41 vol%, 42 vol%, or any value within the range formed by any two of the above point values.
[0089] The above-mentioned preparation method of the present application obtains spherical particles with low specific surface area and good fluidity by spheroidizing and pre-sintering silicon carbide powder, thereby reducing the amount of wax-based binder used and increasing the solid content of silicon carbide ceramic printing materials.
[0090] In a second aspect of the present application, a silicon carbide ceramic printing material is provided, which is prepared by the above-mentioned method for preparing the silicon carbide ceramic printing material.
[0091] In a third aspect of the present application, a silicon carbide ceramic product is provided, the raw materials for preparing the silicon carbide ceramic printing material comprising the above-mentioned silicon carbide ceramic printing material.
[0092] In some embodiments, the method for preparing the silicon carbide ceramic product comprises the following steps:
[0093] The silicon carbide ceramic printing material is used to perform melt deposition forming to obtain a silicon carbide ceramic blank;
[0094] The blank is subjected to degreasing treatment and sintering treatment to obtain a silicon carbide ceramic product.
[0095] The silicon carbide ceramic product of the present application has the advantages of low porosity and good dimensional accuracy.
[0096] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.
[0097] Example 1
[0098] (1) Silicon carbide powder and sintering aid powder are mixed, and a small amount of organic binder is added to prepare a slurry with a certain solid content; the slurry is sprayed into a granulation tower by a sprayer for spray granulation to obtain particles with good fluidity; since the atomized slurry is in the form of fine droplets and has a large specific surface area, the water in the droplets evaporates quickly and granulated powder is obtained by rapid drying; then sieving to obtain silicon carbide composite particles.
[0099] Among them, the average particle size of silicon carbide powder is 0.5μm; the sintering aid powder is boric acid, and its addition amount is 0.5wt% of the total mass of silicon carbide powder; the organic binder is polyvinyl alcohol, and its addition amount is 0.2wt% of the total mass of silicon carbide powder; the temperature of spray granulation is 100°C; the average particle size of the composite particles is 50μm.
[0100] (2) The composite particles obtained in step (1) are placed in a calcining furnace for pre-sintering, and sieved to obtain uniformly distributed silicon carbide spherical particles.
[0101] The pre-sintering temperature is 1200°C and the time is 80 minutes.
[0102] (3) The silicon carbide spherical particles obtained in step (2) are poured into a preheated internal mixer for mixing, and a wax-based binder is added; the mixed mixture is then placed into a granulator for granulation to prepare a granular silicon carbide ceramic printing material.
[0103] Among them, the volume fraction of silicon carbide spherical particles is 60 vol%, and the volume fraction of the wax-based binder is 40 vol%; the wax-based binder includes 85 wt% carnauba wax, 4 wt% ultra-high molecular weight polypropylene (average molecular weight of 1.3 million, melt index of 0.15 g / 10 min), 4 wt% ultra-high molecular weight polyethylene (average molecular weight of 1.2 million, melt index of 0.2 g / 10 min) and 7 wt% stearic acid; the temperature of the mixing treatment is 140°C, and the mixing treatment time is 60 min; the nozzle temperature of the granulation treatment is 120°C, and the screw temperature is 130°C.
[0104] (4) The granular silicon carbide ceramic printing material is formed into a silicon carbide ceramic body by melt deposition molding; and a silicon carbide ceramic product is further obtained by degreasing and sintering.
[0105] The volume fraction of the powder solid phase in the silicon carbide ceramic printing material prepared in Example 1 is 60 vol%; the relative density of the silicon carbide ceramic product is calculated by the Archimedean drainage method, and the porosity of the silicon carbide ceramic product is further calculated to be 4%; the dimensional accuracy is tested with reference to GB / T 39329-2020 "Additive Manufacturing-Test Method-Standard Test Piece Accuracy Inspection", and the dimensional accuracy of the silicon carbide ceramic product is better than the IT11 level (ie, the error value ≤0.160mm / 100mm), and there is no interlayer crack or warping.
[0106] Figure 1 This is a morphology diagram of the silicon carbide ceramic product prepared in Example 1.
[0107] Example 2
[0108] (1) Silicon carbide powder and sintering aid powder are mixed, and a small amount of organic binder is added to prepare a slurry with a certain solid content; the slurry is sprayed into a granulation tower by a sprayer for spray granulation to obtain particles with good fluidity; since the atomized slurry is in the form of fine droplets and has a large specific surface area, the water in the droplets evaporates quickly and granulated powder is obtained by rapid drying; then sieving to obtain silicon carbide composite particles.
[0109] Among them, the average particle size of silicon carbide powder is 1 μm; the sintering aid powder is boron carbide, and its addition amount is 0.8wt% of the total mass of silicon carbide powder; the organic binder is methyl cellulose, and its addition amount is 0.5wt% of the total mass of silicon carbide powder; the temperature of spray granulation is 110°C; and the average particle size of the composite particles is 80 μm.
[0110] (2) The composite particles obtained in step (1) are placed in a calcining furnace for pre-sintering, and sieved to obtain uniformly distributed silicon carbide spherical particles.
[0111] The pre-sintering temperature is 1300°C and the time is 60 minutes.
[0112] (3) The silicon carbide spherical particles obtained in step (2) are poured into a preheated internal mixer for mixing, and a wax-based binder is added; the mixed mixture is then placed into a granulator for granulation to prepare a granular silicon carbide ceramic printing material.
[0113] Among them, the volume fraction of silicon carbide spherical particles is 62 vol%, and the volume fraction of the wax-based binder is 38 vol%; the wax-based binder includes 90 wt% carnauba wax, 6 wt% ultra-high molecular weight polyethylene (average molecular weight of 1 million, melt index of 0.5 g / 10 min) and 4 wt% stearic acid; the mixing temperature is 150 ° C, and the mixing time is 40 min; the nozzle temperature of the granulation process is 130 ° C, and the screw temperature is 140 ° C.
[0114] (4) The granular silicon carbide ceramic printing material is formed into a silicon carbide ceramic body by melt deposition molding; and a silicon carbide ceramic product is further obtained by degreasing and sintering.
[0115] The volume fraction of the powder solid phase in the silicon carbide ceramic printing material prepared in Example 2 is 62 vol%; the relative density of the silicon carbide ceramic product is calculated by the Archimedean drainage method, and the porosity of the silicon carbide ceramic product is further calculated to be 3.5%; the dimensional accuracy of the silicon carbide ceramic product is better than the IT11 level, and there is no interlayer crack or warping.
[0116] Example 3
[0117] (1) Silicon carbide powder and sintering aid powder are mixed, and a small amount of organic binder is added to prepare a slurry with a certain solid content; the slurry is sprayed into a granulation tower by a sprayer for spray granulation to obtain particles with good fluidity; since the atomized slurry is in the form of fine droplets and has a large specific surface area, the water in the droplets evaporates quickly and granulated powder is obtained by rapid drying; then sieving to obtain silicon carbide composite particles.
[0118] Among them, the average particle size of silicon carbide powder is 2μm; the sintering aid powder is boron carbide, and its addition amount is 1wt% of the total mass of silicon carbide powder; the organic binder is methyl cellulose, and its addition amount is 0.5wt% of the total mass of silicon carbide powder; the temperature of spray granulation is 120℃; the average particle size of the composite particles is 100μm.
[0119] (2) The composite particles obtained in step (1) are placed in a calcining furnace for pre-sintering, and sieved to obtain uniformly distributed silicon carbide spherical particles.
[0120] The pre-sintering temperature is 1400°C and the time is 30 minutes.
[0121] (3) The silicon carbide spherical particles obtained in step (2) are poured into a preheated internal mixer for mixing, and a wax-based binder is added; the mixed mixture is then placed into a granulator for granulation to prepare a granular silicon carbide ceramic printing material.
[0122] Among them, the volume fraction of silicon carbide spherical particles is 65 vol%, and the volume fraction of the wax-based binder is 35 vol%; the wax-based binder includes 92 wt% carnauba wax, 5 wt% ultra-high molecular weight polypropylene (average molecular weight of 1.5 million, melt index of 0.1 g / 10 min) and 3 wt% stearic acid; the mixing temperature is 150 ° C, and the mixing time is 60 min; the nozzle temperature of the granulation process is 140 ° C, and the screw temperature is 150 ° C.
[0123] (4) The granular silicon carbide ceramic printing material is formed into a silicon carbide ceramic body by melt deposition molding; and a silicon carbide ceramic product is further obtained by degreasing and sintering.
[0124] The volume fraction of the powder solid phase in the silicon carbide ceramic printing material prepared in Example 3 is 65 vol%; the relative density of the silicon carbide ceramic product is calculated by the Archimedean drainage method, and the porosity of the silicon carbide ceramic product is further calculated to be 2%; the dimensional accuracy of the silicon carbide ceramic product is better than the IT11 level, and there is no interlayer crack or warping.
[0125] Example 4
[0126] The method is basically the same as Example 1, except that the type of the backbone binder is different. In this embodiment, 8 wt% of ultra-high molecular weight polypropylene with an average molecular weight of 1.2 million and a melt index of 0.3 / 10min is used instead of 4 wt% ultra-high molecular weight polyethylene and 4 wt% ultra-high molecular weight polypropylene. Other process conditions and parameters are the same as those in Example 1.
[0127] Example 5
[0128] The method is basically the same as Example 1, except that the type of the backbone binder is different. In this embodiment, 8 wt% of ultra-high molecular weight polyethylene is used instead of 4 wt% of ultra-high molecular weight polyethylene and 4 wt% of ultra-high molecular weight polypropylene. Other process conditions and parameters are the same as those in Example 1.
[0129] Comparative Example 1
[0130] The method is basically the same as Example 1, except that the mixture of silicon carbide powder, sintering aid powder and organic binder is not subjected to spray granulation, that is, the mixture is directly subjected to pre-sintering. Other process conditions and parameters are the same as those in Example 1.
[0131] The solid volume fraction of the silicon carbide ceramic printing material prepared in Comparative Example 1 is 55 vol%, the porosity of the silicon carbide ceramic product printed using the printing material reaches 7.0%, the dimensional accuracy is IT16 level, and warping occurs. Figure 2 is a morphology diagram of the silicon carbide ceramic product obtained in Comparative Example 1; Figure 2 It can be seen that the sample prepared in Comparative Example 1 has cracks between layers due to internal stress.
[0132] Comparative Example 2
[0133] The method is basically the same as Example 1, except that the method does not include the step of pre-sintering the composite particles, that is, the composite particles are directly mixed with the wax-based binder and granulated. Other process conditions and parameters are the same as those in Example 1.
[0134] The solid volume fraction of the silicon carbide ceramic printing material prepared in Comparative Example 2 is 57 vol%, the porosity of the silicon carbide ceramic product printed using the printing material reaches 6.5%, the dimensional accuracy is less than IT11 level, and interlayer cracking occurs.
[0135] Comparative Example 3
[0136] The method is basically the same as Example 1, except that the type of the backbone binder is different. In this comparative example, 8wt% of polypropylene is used instead of 4wt% of ultra-high molecular weight polyethylene and 4wt% of ultra-high molecular weight polypropylene, wherein the average molecular weight of the polypropylene is 500,000 and the melt index is 0.3g / 10min. Other process conditions and parameters are the same as those in Example 1.
[0137] The solid volume fraction of the silicon carbide ceramic printing material prepared in Comparative Example 3 is 60 vol%, the porosity of the silicon carbide ceramic product printed using the printing material reaches 4.5%, the dimensional accuracy is less than IT11 level, and interlayer cracking occurs.
[0138] Comparative Example 4
[0139] The method is basically the same as Example 1, except that the type of the backbone binder is different. In this comparative example, 8 wt% of ultra-high molecular weight polypropylene with an average molecular weight of 800,000 and a melt index of 0.8 g / 10 min is used instead of 4 wt% ultra-high molecular weight polyethylene and 4 wt% ultra-high molecular weight polypropylene. Other process conditions and parameters are the same as those in Example 1.
[0140] The solid phase volume fraction of the silicon carbide ceramic printing materials prepared in the above embodiments and comparative examples of the present application, as well as the porosity and dimensional accuracy parameters of the silicon carbide ceramic products prepared in the above embodiments and comparative examples are shown in Table 1.
[0141] Table 1
[0142]
[0143] It can be seen from the above table that the solid phase volume fraction of the silicon carbide ceramic printing material prepared in the embodiment of the present application is more than 60%; the porosity of the silicon carbide ceramic product prepared using the above printing material is less than 5%, and the dimensional accuracy is better than IT11 level.
[0144] In Comparative Example 1, the mixture of silicon carbide powder, sintering aid and organic binder was not spheroidized to obtain nearly spherical composite particles. As a result, the irregularly shaped silicon carbide powder would produce more voids when stacked, thereby increasing the solid phase volume fraction; and the specific surface area of the silicon carbide powder that has not been spray granulated is relatively low, so the sintering activity is relatively poor, resulting in warping of the silicon carbide ceramic product after sintering.
[0145] In Comparative Example 2, the composite particles were not pre-sintered, and the composite particles may be broken during the mixing process, thereby causing cracks in the prepared silicon carbide ceramic product.
[0146] In Comparative Example 3, low molecular weight polypropylene is used as the backbone binder, which may affect the strength of the product during the solvent degreasing process, so that the final silicon carbide ceramic product has a lower porosity but a reduced dimensional accuracy and warping.
[0147] The melt index of the ultra-high molecular weight polypropylene in Comparative Example 4 is 0.8 g / 10 min, and the silicon carbide ceramic product finally obtained has a large porosity and cracks appear between the layers.
[0148] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0149] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A method for preparing a silicon carbide ceramic printing material, characterized in that: The steps include: The silicon carbide powder, sintering aid and organic binder are mixed and spheroidized to obtain composite particles; Pre-sintering the composite particles to obtain spherical particles; The spherical particles are mixed with a wax-based binder, and kneading and granulation are performed in sequence to obtain the silicon carbide ceramic printing material; Among them, calculated by mass percentage, the wax-based adhesive includes 85% to 92% wax adhesive, 5% to 8% backbone adhesive and 1% to 8% dispersant, the melting index of the backbone adhesive is 0.1 g / 10min to 0.5 g / 10min, and the average molecular weight of the backbone adhesive is 1 million to 1.5 million.
2. The method for preparing a silicon carbide ceramic printing material according to claim 1, characterized in that: The preparation method meets one or more of the following characteristics: (1) The backbone binder includes one or more of ultra-high molecular weight polypropylene and ultra-high molecular weight polyethylene; (2) The wax binder includes one or more of carnauba wax, paraffin wax and microcrystalline wax; (3) The dispersant includes one or more of stearic acid, zinc stearate and epoxy resin.
3. The method for preparing a silicon carbide ceramic printing material according to claim 1, characterized in that: The spheroidization treatment includes one or more of spray granulation and ultrasonic spray drying; Optionally, the temperature of the spray granulation is 80°C to 120°C.
4. The method for preparing the silicon carbide ceramic printing material according to any one of claims 1 to 3, characterized in that: The preparation method meets one or more of the following characteristics: (1) The D50 particle size of the silicon carbide powder is 0.2 μm to 2 μm; (2) The D50 particle size of the composite particles is 20 μm to 200 μm; (3) The average particle size of the spherical particles is 50 μm to 100 μm.
5. The method for preparing the silicon carbide ceramic printing material according to any one of claims 1 to 3, characterized in that: The preparation method meets one or more of the following characteristics: (1) The sintering aid includes one or more of boric acid, boron, boron carbide, yttrium oxide and aluminum oxide; (2) The organic binder includes one or more of polyvinyl alcohol, polyethylene glycol, methyl cellulose and polyacrylic acid.
6. The method for preparing the silicon carbide ceramic printing material according to any one of claims 1 to 3, characterized in that: The preparation method meets one or more of the following characteristics: (1) Based on the total mass of silicon carbide powder, the amount of the sintering aid added is 0.2wt%~2wt%; (2) Based on the total mass of the silicon carbide powder, the amount of the organic binder added is 0.1wt%~0.5wt%.
7. The method for preparing the silicon carbide ceramic printing material according to any one of claims 1 to 3, characterized in that: The preparation method meets one or more of the following characteristics: (1) The pre-sintering treatment is performed at a temperature of 1000°C to 1400°C and for a time of 30 min to 120 min; (2) The mixing process is performed at a temperature of 120°C to 180°C and for a time of 40 min to 80 min; (3) The nozzle temperature of the granulation process is 120°C to 140°C, and the screw temperature is 120°C to 150°C.
8. The method for preparing the silicon carbide ceramic printing material according to any one of claims 1 to 3, characterized in that: Based on the total volume of the spherical particles and the wax-based binder, the spherical particles account for 58 vol% to 65 vol%, and the wax-based binder accounts for 35 vol% to 42 vol%.
9. A silicon carbide ceramic printing material, characterized in that: The silicon carbide ceramic printing material is prepared by the preparation method of any one of claims 1 to 8.
10. A silicon carbide ceramic product, characterized in that: The raw materials for preparing the same include the silicon carbide ceramic printing material described in claim 9.